Dynamic simulation of falling weight deflectometer tests on flexible transversely isotropic layered pavements. Issue 139 (December 2020) - Han, Zejun; Yang, Linqing; Fang, Hongyuan; Zhang, Jin
Abstract: Developing an accurate and efficient forward model of the dynamic response of pavement structure is of great significance for obtaining the design parameters of the layered pavement structure through inverse calculation based on the measured pavement data. Based on the spectral element method, this study proposes an accurate and efficient numerical dynamic model of falling weight deflectometer tests for the transversely isotropic layered pavement structure. The developed algorithm considerably enhances the efficiency of the model in solving the dynamic response of transversely isotropic layered media by avoiding the infinite integration in integral transformation. Moreover, numerical examples verify the accuracy and efficiency of the algorithm developed in this study. At the same time, an extensive parametric studies have been carried out to clarify the effects of the Young's modulus in the vertical direction and thickness of the layered pavement structure as well as the elastic modulus of the thin interlayer on the dynamic response of the pavement, which provides a reliable, numerical, theoretical basis for the design of pavement structure. Highlights: A new spectral element method (SEM) for cross-anisotropic layered media is presented. A forward model of the dynamic response of pavement structure is developed based on the new SEM. The infinite integration in integral transformation is avoided. The method has high accuracy and efficiency. An extensive parameter analysis is conducted on the properties of the layered pavement structures.